A Quantitative Study: Elementary School Students’ Mastery of Multiplication and Division Concepts through the Drill and Practice Method - Mindo H. Sinambela; Christine M. Rumpaisum; Citra R. Napitupulu; Titin A. Nainggolan (Madako Elementary School, 2026)
This study originates from the suboptimal understanding of the concepts of multiplication and division among elementary school students, which should serve as an important foundation for learning more complex mathematics material. This study aims to test the effectiveness of the drill and practice method in improving mastery of these concepts. The approach used is quantitative with a quasi-experimental design of the one-group pretest-posttest type, involving 13 students as a saturated sample from the Shallom Wamena Sunday School community. Data collection was carried out through tests and documentation, then analyzed using a paired sample t-test and N-Gain at a significance level of 0.05 with the help of SPSS 23. The results showed a statistically significant increase (Sig. 0.012 < 0.05) after the application of the method, although the level of improvement based on N-Gain (0.30) was classified as low. These findings indicate that the drill and practice method is effective but not yet optimal in improving deep conceptual understanding. The implications confirm the importance of developing a learning design that not only focuses on repetitive exercises, but also the need to integrate a more constructivistic, contextual, and interaction-based approach to maximize the impact of the results of the method.